Incorporating neck biomechanics in helmet testing: Evaluation of commercially available WaveCel helmets. (April 2022) - Chung, Vivian W.J.; Dias, Luis; Booth, Gabrielle; Cripton, Peter A.
Abstract: Background: Cycling helmets often incorporate elements aimed to dissipate rotational energies, which is widely acknowledged to play a key role in concussion mechanics. In this study, we investigated the mechanics of an oblique helmet test protocol that induced helmet rotation while using it to evaluate the effectiveness of three helmet models: two standard expanded polystyrene helmets and a commercially-available helmet equipped with a liner designed to mitigate linear and rotational energies. Methods: Helmets equipped with WaveCel were tested against two expanded polystyrene helmet models through guided drops using a Hybrid III (HIII) head-and-neck surrogate. The three helmet models were tested across four impact conditions ( n = 5) of different speeds and impact surface angles. Findings: Across all tests, a similar sequence of head motion was observed – first a flexion phase followed by an extension phase. The extension phase lacked evidence of biofidelity and was likely attributable to the energy stored in the neckform during the flexion phase; it was therefore neglected from analysis. Results showed WaveCel reduced the probability of AIS2 head injury across all tests (3 to 27% reductions in 4.8 m/s impacts; 36 to 37% reductions in 6.2 m/s impacts). Interpretation: The two-phased response of the HIII suggests that boundary condition selection can influence results and should thus be reported in studies using similar methods. While this protocol involved both axial and tangential impact components and were thus representative of real-world collisions, the efficacy of WaveCel should be further investigated through additional laboratory studies and tracking real-world cycling injury statistics. Highlights: WaveCel helmets found to be effective in reducing peak rotational velocities in oblique impacts Hybrid III test neck was found to exhibit high rebounding energy, resulting in a two-phased motion The rebounding second phase was likely non-biofidelic based on current literature evidence It is vital for studies using single-axis kinematic data to declare definition of peak values